A New Modified Twist Drill Craniostomy Using a Novel Device to Evacuate Chronic Subdural Hematoma. Issue 10 (March 2016) - Wang, Qing-Feng; Cheng, Cheng; You, Chao
Abstract : Abstract: Compared with burr hole craniostomy (BHC), twist drill craniostomy (TDC) is increasingly popular because of its minimal invasiveness in evacuating chronic subdural hematoma (CSDH). However, the TDC technique varies and is continually developing; moreover, no consensus yet exists regarding the optimal protocol, and the efficacy and safety of TDC is still controversial, especially with respect to a specific method. This article introduces a new modified TDC technique using a novel device, the YL-1 puncture needle, and evaluates its efficacy and advantages compared with BHC. A retrospective study involving 121 patients with CSDH who underwent surgery at a single center was conducted, involving 68 patients undergoing modified TDC (TDC group) and 53 patients treated by BHC (BHC group). The neurological outcome was studied to evaluate the surgery efficacy, and the radiological outcome was assessed as a supplement to the surgery efficacy. In addition, complications, recurrence, and reoperation, as well as pneumocrania, operation duration, and length of stay, were studied to evaluate the advantages of the modified TDC compared with BHC. Independent sample t tests or rank-sum tests were used to compare the outcomes between the 2 groups. The neurological and radiological outcomes did not differ significantly between the TDC and BHC groups ( P  = 0.852 and P  = 0.232, respectively), while the rates of complication and pneumocrania in patients who underwent the modified TDC were significantly lower than that in those who underwent BHC ( P  = 0.021 and P  < 0.001, respectively). The recurrence and reoperation rates in patients from the 2 groups were similar ( P  = 0.566 and P  = 0.715, respectively). The operation duration and length of hospital stay of the patients who underwent the modified TDC were significantly shorter than those of the patients who underwent BHC (both P  < 0.001). Modified TDC with a YL-1 puncture needle is a minimally invasive surgical technique to treat CSDH; this procedure is as effective as BHC, but safer and simpler than BHC, and should be considered for patients with CSDH, especially the elderly.